PENGARUH PEMBERIAN INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA GURU TAMAN KANAK - KANAK DI KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Jumiati, Jumiati; Syukri, M.; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Teacher performance is the ability of a teacher to carry out learning task at school,expecially at the pre-school age and responsible for students under his guidance by increasing the creativity of studens' learning.Providing incentives to teachers is one form of activity carried out by the government in order to improve teacher performance. While work motivation is the driving force that causes people to act to achieve goals by making changes for the better.The purpose of the study was to determine the effect of providing incentives and work motivation on the performance of kindergarten teachers in sungai Ambawang district,Kubu raya Regency.Descriptive research desaign with a sample of 36respondents and analyzed by multiple regression data with a statictical product and Servis Solution (SPSS).The results show that: (1)The Provision of non material incentives to techer performance is appropriate.(2) The Provision of non material incentives for teacher performance is appropriate (3)The Provision of incentives has a partially significant effect on teacher performance.(4)Teacher work motivation has a partially significant effect on teacher performance.(5)The multiple regression analysis test concluded that the Provision of incentives and work motivation has a simultaneous effect on techer performance.From the results of research data analysis shows that the magnitude of the effect of incentives and work motivation on teacher performance is 47.9% while the rest is influenced by other variables.The better the Provision of incentives and work motivation for teachers,the resulting performance can increase better.